The Effectiveness of Science Learning Research Skills: A Meta-Analysis Study - Ipin Aripin; Topik Hidayat; Nuryani Rustaman; Riandi Riandi (Scientiae Educatia: Jurnal Pendidikan Sains, 2021)
Research skills are our ability to find and answer a question or solve a problem. This study aimed to identify methods in the science learning of research skills. Meta-analysis study used PRISMA(Preferred Reporting Items for Systematic reviews and Meta-Analyses) method. The stages of the research method include: determining criteria and literature search techniques, conducting literature analysis, coding, and data analysis. Jeffreys's Amazing Statistics Program (JASP) version 0.14.1 was used as a data analysis tool. A total of (n=16) articles were taken from Indonesia and overseas being analyzed. Research findings showed that learning through research skills gave effect around 0.63 (medium). The Inquiry method was the most effective and used in learning through research skills. Based on the research findings above,  it can be concluded that there were ten effective methods in learning through research skills. The inquiry method could be recommended in the learning through research skills in the schools and college level.